Images of rebirt h cognitive poetics and transformational soteriology in the Gospel of Philip and the Exegesis on the Soul - Lundhaug, Hugo. (Nag Hammadi and Manichaean Studies, 2010)
This book offers fresh readings of the Gospel of Philip (NHC II.3) and the Exegesis on the Soul (NHC II.6) from new theoretical and historical perspectives. Eschewing the category of "Gnosticism" and challenging common categorisations, the book analyses the preserved Coptic texts as coherent Christian compositions contemporary with the production and use of the Nag Hammadi Codices. A methodological framework based on Cognitive Poetics is outlined and applied to illuminate how the texts present a soteriology of transformation through religious rituals and practices using complex conceptual and intertextual blends with important polemical and paraenetic functions. The analysis highlights the use of metaphors and allusions in (re-)interpretations of authoritative Scripture, ritual and dogma. Complete Coptic texts and translations are included.